The cellular interactome for glycoprotein 5 of the Chinese highly pathogenic porcine reproductive and respiratory syndrome virus - Ji-ge DU; Xin-na GE; Hong DONG; Ning ZHANG; Lei ZHOU; Xin GUO; Han-chun YANG (Journal of Integrative Agriculture, 2016)
The glycoprotein 5 (GP5) of porcine reproductive and respiratory syndrome virus (PRRSV) is a multi-functional protein that plays important roles in virus assembly, entry and viral anti-host responses. In the present study, we investigated the cellular binding partners of GP5 by using lentivirus transduction coupled with immunoprecipitation and mass spectrometry. There were about 40 cellular proteins identified with high Confidence Icons by MS/MS. Ingenuity Pathway Analysis (IPA) indicated that these proteins could be assigned to different functional classes and networks. Furthermore, we validated some of the interactions by co-immunoprecipitation (Co-IP) and confocal microscopy, including those with mitofilin, a mitochondrial inner membrane protein that might be involved in PRRSV or GP5-induced apoptosis, and calnexin, a protein chaperone that might facilitate the folding and maturation of GP5. The interactome data contribute to understand the role and molecular mechanisms of GP5 in PRRSV pathogenesis.